2020
DOI: 10.1101/2020.09.30.319988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bisphenol-S and Bisphenol-F alter mouse pancreatic β-cell ion channel expression and activity and insulin release through an estrogen receptor ERβ mediated pathway

Abstract: Bisphenol-S (BPS) and Bisphenol-F (BPF) are current Bisphenol-A (BPA) substitutes. Here we used pancreatic β-cells from wild type (WT) and estrogen receptor β (ERβ) knockout (BERKO) mice to investigate the effects of BPS and BPF on insulin secretion, and the expression and activity of ion channels involved in β-cell function. BPS or BPF rapidly increased insulin release and diminished ATP-sensitive K+ (KATP) channel activity. Similarly, 48 h treatment with BPS or BPF enhanced insulin release and decreased the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…6g-i). Of note, positive values indicate strong ligand-protein binding (Marroqui et al, 2021). E2 binding to both homodimer cavities, LBD-ERαα (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6g-i). Of note, positive values indicate strong ligand-protein binding (Marroqui et al, 2021). E2 binding to both homodimer cavities, LBD-ERαα (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bisphenol-A (BPA), which is used as a model of endocrine disrupting chemical that alters insulin secretion and insulin sensitivity in mice (Alonso-Magdalena et al, 2010, 2006), has been implicated in the etiology of diabetes (Alonso-Magdalena et al, 2011; Sargis and Simmons, 2019). At concentrations similar to those found in human blood (Vandenberg et al, 2010), BPA increases pancreatic insulin content via ERα (Alonso-Magdalena et al, 2008) and regulates ion channel expression and function as well as augments insulin release in an ERβ-mediated manner (Marroqui et al, 2021; Martinez-Pinna et al, 2019; Soriano et al, 2012). In INS-1 cells and mouse dispersed islet cells, BPA induces mitochondrial dysfunction, ROS production and NF-κB activation, which culminates in beta cell apoptosis (Carchia et al, 2015; Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…To date, only one study has been published exploring BPS action. This study showed that mouse islets of Langerhans treated with 1 nM and 1 μM BPS exhibited enhanced insulin release compared to controls [37].…”
Section: Discussionmentioning
confidence: 99%